Generalized 2D polynomial chaotic map and its application in information transmission - Wenhao YAN; Zijing JIANG; Xin HUANG; Shujuan ZHU; Qun DING (Tongxin xuebao)
Existing chaotic systems have many defects in engineering applications, such as discontinuous chaotic parameter range, weak chaos, uneven output of chaotic sequences and dynamic degradation.Therefore, a generalized 2D polynomial chaotic mapping model was proposed.By setting different control parameters and the highest degree of polynomial, a series of 2D robust chaotic maps with specific Lyapunov exponent could be obtained.In order to avoid the output of the second state equation collapsing to a fixed value, a random disturbance variable which did not change with time was introduced.Finally, a numerical example was given to verify the effectiveness of the proposed model, and the dynamic analysis showed that the mapping has complex dynamic behavior.Finally, the system was applied to information transmission technology.Compared with other chaotic maps, the system can achieve lower bit error rate, which indicates that the chaotic map is more suitable for chaotic information transmission.